2022
DOI: 10.3390/ma15248816
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric, Electrochemical, & Dielectric Properties of Four ZnO Nanostructures

Abstract: In this work, we investigated the thermoelectric, electrochemical, and dielectric properties of four different ZnO morphologies, namely nanoribbons, nanorods, nanoparticles, and nanoshuttles. Temperature-dependent Seebeck coefficients were observed using thermoelectric measurements, which confirmed that all synthesized ZnO nanostructures are n-type semiconductors. The Van der Pauw method was applied to measure electrical conductivity, which was also used to calculate the thermal activation energy. Electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Bui et al synthesised oxide (ZnO) NWs (NWs) with diameters ranging from 50 to 210 nm using CVD and investigated the diameter-dependent thermal transport, concluding that there is a significant reduction in thermal conductivity of (ZnO) NWs (NWs) compared to bulk ZnO due to increased phonon boundary scattering [ 253 ]. Rusiri et al (2022) investigated the effect of ZnO morphology, such as nanoribbons, nanorods, nanoparticles, and nanoshuttles, on the TE performance and found that the highest performance can be achieved using ZnO NRDs [ 254 ].…”
Section: One-dimensional Thermoelectric Materialsmentioning
confidence: 99%
“…Bui et al synthesised oxide (ZnO) NWs (NWs) with diameters ranging from 50 to 210 nm using CVD and investigated the diameter-dependent thermal transport, concluding that there is a significant reduction in thermal conductivity of (ZnO) NWs (NWs) compared to bulk ZnO due to increased phonon boundary scattering [ 253 ]. Rusiri et al (2022) investigated the effect of ZnO morphology, such as nanoribbons, nanorods, nanoparticles, and nanoshuttles, on the TE performance and found that the highest performance can be achieved using ZnO NRDs [ 254 ].…”
Section: One-dimensional Thermoelectric Materialsmentioning
confidence: 99%
“…Also, the asymmetric configuration of Au-Al2O3-Cu2O-Cu shows superior characteristics among all compared configurations. The lesser difference of bandgap and electron affinities of used metals and insulators (see Table 2 [33][34][35][36]) for the symmetric metals case i.e. Au-Al2O3-Cu2O-Au configuration makes it less efficient.…”
Section: Rectification Characterization Of Miim Rectennamentioning
confidence: 99%
“…For decades, zinc oxide (ZnO) nanoparticles (NPs) have attracted considerable interest of the research community in different areas of science and technology due to the fundamental importance as well as huge potentials for application of these materials in devices (e.g., optoelectronic, nanopiezotronics, nanogenerator, nanosensor, laser applications, high dielectric application, solar cells, and photocatalysis). [1][2][3][4][5][6][7][8][9][10][11] ZnO with wide direct bandgap energy (3.1-3.3 eV) and high excitation binding energy (60-100 meV) is a well-known II-VI n-type semiconducting material. [12] It crystallizes in a stable hexagonal wurtzite structure where the Zn and O atoms have highly ionic bonding.…”
Section: Introductionmentioning
confidence: 99%